1996
DOI: 10.1016/0014-2999(96)00101-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of postischemic brain damage and memory deficits following treatment with the selective adenosine A1 receptor agonist

Abstract: Agonists of adenosine A1 receptors have been frequently proposed as candidates for clinical development in treatment of cerebral ischemia and stroke. Numerous experimental studies have shown that pre- and postischemic administration of these drugs results in a very significant reduction of postischemic brain damage. However, only a few studies determined the impact of cerebral ischemia and drug treatment on postischemic recovery of spatial memory. The present paper demonstrates that preischemic i.p. administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 24 publications
3
24
1
Order By: Relevance
“…In this study, we found that, in permanent ischemia, the neuroprotective effect of CX3CL1 is lost in rats treated with DPCPX and in A 1 R Ϫ/Ϫ mice, suggesting that the involvement of A 1 R in CX3CL1-induced neuroprotection is conserved from cellular to in vivo models. This agrees with data indicating the importance of A 1 R activation in neuroprotection, reducing neuronal injury in vitro and in vivo and being involved in mechanisms of ischemic preconditioning (Von Lubitz et al, 1996;Nakamura et al, 2002). Acute A 1 R activation reduces neuronal damage, whereas A 1 R antagonists potentiate damage in neuronal cultures, brain slices, and animal models of cerebral ischemia, epileptic models, and brain trauma (Olsson et al, 2004;Cunha, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found that, in permanent ischemia, the neuroprotective effect of CX3CL1 is lost in rats treated with DPCPX and in A 1 R Ϫ/Ϫ mice, suggesting that the involvement of A 1 R in CX3CL1-induced neuroprotection is conserved from cellular to in vivo models. This agrees with data indicating the importance of A 1 R activation in neuroprotection, reducing neuronal injury in vitro and in vivo and being involved in mechanisms of ischemic preconditioning (Von Lubitz et al, 1996;Nakamura et al, 2002). Acute A 1 R activation reduces neuronal damage, whereas A 1 R antagonists potentiate damage in neuronal cultures, brain slices, and animal models of cerebral ischemia, epileptic models, and brain trauma (Olsson et al, 2004;Cunha, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Substantial studies have shown that pre-and postischemic administration of these drugs result in a significant reduction of postischemic brain damage while A 1 receptor antagonists blocked such neuroprotection effect induced by adenosine and its analogue. [29][30][31] We hypothesized that adenosine and the adenosine A1 receptor were essential for the induction of ischemic tolerance induced by isoflurane preconditioning in the brain. The results of the present study prove that the neuroprotection induced by isoflurane pretreatment was significantly attenuated by DPCPX.…”
Section: Discussionmentioning
confidence: 99%
“…A 1 receptor agonists have been claimed to play a pivotal role in protection from hypoxic insults (Sebastião et al, 2001). A 1 receptor activation decreases cytotoxic amino acid release from both neurons and glial cells (Schubert et al, 1994;Von Lubitz et al, 1996;Pearson et al, 2006). A 1 receptor agonists were particularly effective against cerebral ischemia (Von Lubitz et al, 1994, 1999Chen et al, 2006) and cerebral ischemia preconditioning (Heurteaux et al, 1995).…”
Section: Ischemiamentioning
confidence: 99%